2021
DOI: 10.3390/pharmaceutics13111900
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofiber and Cryogel of Polyvinyl Alcohol Transdermal Patch Containing Diclofenac Sodium: Preparation, Characterization and In Vitro Release Studies

Abstract: Transdermal drug delivery systems (TDDS) have drawn more interest from pharmaceutical scientists because they could provide steady blood levels and prevent the first-pass metabolism over a longer period. Polyvinyl alcohol (PVA) has been widely used in this application due to its biocompatibility, non-toxicity, nanofiber and hydrogel-forming ability. Despite those benefits, their morphology would easily be destroyed by continuous water absorption and contribute to burst drug release due to its hydrophilicity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Any comparison of the current study’s results with other intervention programs for soft tissue injuries to assess the effectiveness of DK gel compared to other established products is hampered by differences in study design, inclusion criteria, duration of treatment, and efficacy assessment methods. Furthermore, in recent years, a variety of biomaterials (e.g., patches-based hydrogels, cryogels, nanofibers) together with their distinct physicochemical features have been extensively investigated and developed in the fields of drug-delivery, tissue engineering, medicine, and public health, including disease diagnosis [ 21 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Thereby, a most recent study in rabbits has reported an injectable thermosenstive hydrogel for dual delivery of diclofenac and avastin (an anti-VEGF) to reduce the inflammation of the corneal neovascularization more effectively [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Any comparison of the current study’s results with other intervention programs for soft tissue injuries to assess the effectiveness of DK gel compared to other established products is hampered by differences in study design, inclusion criteria, duration of treatment, and efficacy assessment methods. Furthermore, in recent years, a variety of biomaterials (e.g., patches-based hydrogels, cryogels, nanofibers) together with their distinct physicochemical features have been extensively investigated and developed in the fields of drug-delivery, tissue engineering, medicine, and public health, including disease diagnosis [ 21 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Thereby, a most recent study in rabbits has reported an injectable thermosenstive hydrogel for dual delivery of diclofenac and avastin (an anti-VEGF) to reduce the inflammation of the corneal neovascularization more effectively [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The permeability assay was operated in a Franz diffusion cell. A cellulose nitrate membrane (skin-mimicking membrane) 41 was first placed in a vertical diffusion cell, the effective surface area of which was 0.64 cm 2 . The suspension of BFZ or BFZ–TPA (containing approximately 50 mg) was prepared and located above the donor compartment, 42 and the recipient chamber was filled with a buffer solution of pH 6.8.…”
Section: Methodsmentioning
confidence: 99%
“…In another research study by Sa’adon et al, electrospun (2 mL and 3 mL solution) PVA (10 wt% in water) fiber mats were prepared and a DS (0.0 (un-medicated), 1.0, 1.5, and 2.0%)-medicated PVA layer was added on the electrospun PVA mats [ 54 ]. The cryogelation of the dual-layered samples was carried out via three freeze–thaw (24 h freeze at −20 °C, 2 h thaw at room temperature) cycles.…”
Section: Electrospinning-based Pva Ddssmentioning
confidence: 99%
“… Cumulative amount of DS release per unit area (mg/cm 2 ) for DS -medicated DL A 3C and DL B 3C [ 54 ]. …”
Section: Figurementioning
confidence: 99%